Friction Stir-Based Techniques: An Overview - El-Zathry, Noah E.; Akinlabi, Stephen; Woo, Wai Lok; Patel, Vivek; Mahamood, Rasheedat M. (Welding in the world, 2025)
Friction stir-based techniques (FSTs), originating from friction stir welding (FSW), represent a solid-state processing method catering to the demands of various industrial sectors for lightweight components with exceptional properties. These techniques have gained much more attraction by providing an opportunity to tailor the microstructure and enhance the performance and quality of produced welds and surfaces. While significant attention has historically been directed towards the FSW process, this review delves into the working principles of FSTs, exploring their influence on mechanical properties and microstructural characteristics of various materials. Additionally, emphasis is placed on elucidating the advancement of hybrid FSW processes for both similar and dissimilar metal components, aimed at enhancing welding quality through meticulous control of grain textures, structures, precipitation, and phase transformations. Finally, the review identifies current knowledge gaps and suggests future research directions. This review paper synthesises academic literature sourced from the Web of Science (WoS) and Scopus databases, supplemented by additional sources such as books from the last 15 years.